Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

A framework for physically consistent storylines of UK future mean sea level rise - Matthew D. Palmer; Benjamin J. Harrison; Jonathan M. Gregory; Helene T. Hewitt; Jason A. Lowe; Jennifer H. Weeks (Climatic Change, 2024)
We present a framework for developing storylines of UK sea level rise to aid risk communication and coastal adaptation planning. Our approach builds on the UK national climate projections (UKCP18) and maintains the same physically consistent methods that preserve component correlations and traceability between global mean sea level (GMSL) and local relative sea level (RSL). Five example storylines are presented that represent singular trajectories of future sea level rise drawn from the underlying large Monte Carlo simulations. The first three storylines span the total range of the Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report (AR6) likely range GMSL projections across the SSP1-2.6 and SSP5-8.5 scenarios. The final two storylines are based upon recent high-end storylines of GMSL presented in AR6 and the recent literature. Our results suggest that even the most optimistic sea level rise outcomes for the UK will require adaptation of up to 1 m of sea level rise for large sections of coastline by 2300. For the storyline most consistent with current international greenhouse gas emissions pledges and a moderate sea level rise response, UK capital cities will experience between about 1 and 2 m of sea level rise by 2300, with continued rise beyond 2300. The storyline based on the upper end of the AR6 likely range sea level projections yields much larger values for UK capital cities that range between about 3 and 4 m at 2300. The two high-end scenarios, which are based on a recent study that showed accelerated sea level rise associated with ice sheet instability feedbacks, lead to sea level rise for UK capital cities at 2300 that range between about 8 m and 17 m. These magnitudes of rise would pose enormous challenges for UK coastal communities and are likely to be beyond the limits of adaptation at some locations.

An Amundsen Sea source of decadal temperature changes on the Antarctic continental shelf - Sybren S. Drijfhout; Christopher Y. S. Bull; Helene Hewitt; Paul R. Holland; Adrian Jenkins; Pierre Mathiot; Alberto Naveira Garabato (Ocean Dynamics, 2024)
Mass loss from the Antarctic Ice Sheet is dominated by basal melting–induced warm ocean water. Ice-sheet mass loss and thinning of buttressing ice shelves occur primarily in the Amundsen and Bellingshausen Seas. Here, we show that in a global ocean simulation using the 0.25° Nucleus for European Modeling of Ocean (NEMO) model driven by the JRA55 reanalysis from 1982 to 2017, the Amundsen sector of the Antarctic continental shelf acts as a gateway, regulating the on-shelf access of warm Circumpolar Deep Water (CDW) from the deep ocean and its westward transfer to other sectors up to ca. 90° E, particularly the Ross Sea. As a result, anomalies in Antarctic-shelf-averaged temperature mainly originate in the Amundsen sector. These changes are primarily governed by shifts in the Amundsen Sea Low associated with tropical climate variability, modulating the on-shelf transport of CDW via wind-driven perturbations to ocean currents. The ensuing temperature anomalies progress westward from the Amundsen Sea via three distinct routes: a slow, convoluted westward pathway on the shelf via the Antarctic Coastal Current; a faster westward pathway along the shelf break via the Antarctic Slope Current and then onto the shelf along topographic troughs; and a third, eastward route toward the Bellingshausen sector, whereby temperature anomalies are transported into a region of local wind-generated changes farther north. These results emphasize the importance of the Amundsen sector for climate variability over the Antarctic shelves.

The benefits of high-resolution models in simulating the Kuroshio Extension and its long-term changes - Bo An; Yongqiang Yu; Helene Hewitt; Peili Wu; Kalli Furtado; Hailong Liu; Pengfei Lin; Yihua Luan; Kangjun Chen (Climate Dynamics, 2023)

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Model-Observations Synergy in the Coastal Ocean - Pierre De Mey-Frémaux; Nadia Ayoub; Alexander Barth; Robert Brewin; Guillaume Charria; Francisco Campuzano; Stefano Ciavatta; Mauro Cirano; Christopher A. Edwards; Ivan Federico; Shan Gao; Isabel Garcia Hermosa; et al. (Frontiers in Marine Science, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Arctic summer sea-ice seasonal simulation with a coupled model: Evaluation of mean features and biases - P P Saheed; Ashis K Mitra; Imranali M Momin; E N Rajagopal; Helene T Hewitt; Ann B Keen; Sean F Milton (Journal of Earth System Science, 2019)

A case study of a modelled episode of low Arctic sea ice - Ann B. Keen; Helene T. Hewitt; Jeff K. Ridley (Climate Dynamics, 2013)

Identifying uncertainties in Arctic climate change projections - Daniel L. R. Hodson; Sarah P. E. Keeley; Alex West; Jeff Ridley; Ed Hawkins; Helene T. Hewitt (Climate Dynamics, 2013)

Monitoring and quantification of inclusion body formation in Escherichia coli by multi-parameter flow cytometry - Fredrik Wållberg; Helene Sundström; Erika Ledung; Christopher J. Hewitt; Sven-Olof Enfors (Biotechnology Letters, 2005)